2021
DOI: 10.3390/cancers13051000
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of Niche-Signalling Pathways in Colorectal Cancer: What Makes and Breaks the Intestinal Stem Cell

Abstract: The intestinal epithelium fulfils pleiotropic functions in nutrient uptake, waste elimination, and immune surveillance while also forming a barrier against luminal toxins and gut-resident microbiota. Incessantly barraged by extraneous stresses, the intestine must continuously replenish its epithelial lining and regenerate the full gamut of specialized cell types that underpin its functions. Homeostatic remodelling is orchestrated by the intestinal stem cell (ISC) niche: a convergence of epithelial- and stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 387 publications
(535 reference statements)
0
12
0
Order By: Relevance
“…CSC niches have already been identified in several types of human cancers including brain, liver, breast, lung, head and neck, prostate, melanoma, gastric, pancreatic, renal, ovarian, esophageal and colorectal cancers [ 75 87 ]. Various studies have focused on the similarities and differences among the niches in different cancers and how cancer specific microenvironments can affect the formation and the development of CSC niches [ 4 , 6 , 88 90 ].…”
Section: The Csc Niche In Different Cancersmentioning
confidence: 99%
“…CSC niches have already been identified in several types of human cancers including brain, liver, breast, lung, head and neck, prostate, melanoma, gastric, pancreatic, renal, ovarian, esophageal and colorectal cancers [ 75 87 ]. Various studies have focused on the similarities and differences among the niches in different cancers and how cancer specific microenvironments can affect the formation and the development of CSC niches [ 4 , 6 , 88 90 ].…”
Section: The Csc Niche In Different Cancersmentioning
confidence: 99%
“…Secretion of BMP ligands by crypt expressing oncogenic KRAS or PI3K, inhibition of ISC activity, and alteration of Wnt signaling by PDGFRloCD81 + stromal cells induced by crypt with oncogenic PI3K 176 . In conclusion, BMP signaling sustains homeostatic balance by suppressing Lgr5 + ISC proliferation at the base of the crypt while promoting the allocation of secretory cell lines 177 .…”
Section: Signaling Pathways Associated With Regulation Of Iscsmentioning
confidence: 93%
“…Interestingly, butyrate also impacts tumorigenesis by regulating intestinal stem cells (ISC), the cells of origin of intestinal cancer [61,62]. A recent study showed butyrate suppressed the intestinal stem cell proliferation in crypts surrounding the ulcers in a mouse model of colitis by acting as an HDACi to promote the expression of the negative cell-cycle regulator Foxo3 [63].…”
Section: The Butyrate Paradoxmentioning
confidence: 99%